PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) DAN AKTIVITAS SETTING LINGKUNGAN TERHADAP HASIL BELAJAR SISWA DALAM MATA PELAJARAN IPA KELAS VI SD NEGERI 002 RAMBAH KABUPATEN ROKAN HULU - -, Darmawati (Edu Research, 2016)
The research aims studying the Influence of Cooperative Learning Model of Team Games Tournament (TGT) Type and Environmental Activity Setting to Students Learning Outcomes in Science Subjects. This experiment research was conducted inSD Negeri 002 Rambah on the First Semester in the academic year 2014-2015. This research involved grade VI which students of VIC as experimental class and VIA grade students as a control class. It is a random sampling. This research uses quasiexperimenta model with 2 x 2 factorial designs. The result of the research of the Influence of Cooperative Learning Model of Team Games Tournament (TGT) Type and Environmental Activity Setting To Students Learning Outcomes in ScienceSubjects shows: (1) The differences in learning outcome of students in science subject taught by using Cooperative Learning model Team Games Tournament (TGT) and conventional learning model.